Reactive Oxygen Species Generation-Scavenging and Signaling during Plant-Arbuscular Mycorrhizal and Piriformospora indica Interaction under Stress Condition - Nath, Manoj; Bhatt, Deepesh; Prasad, Ram; Gill, Sarvajeet S.; Anjum, Naser A.; Tuteja, Narendra (Frontiers in Plant Science, 2016)
A defined balance between the generation and scavenging of reactive oxygen species (ROS) is essential to utilize ROS as an adaptive defense response of plants under biotic and abiotic stress conditions. Moreover, ROS are not only a major determinant of stress response but also acts as signaling molecule that regulates various cellular processes including plant-microbe interaction. In particular, rhizosphere constitutes the biologically dynamic zone for plant–microbe interactions which forms a mutual link leading to reciprocal signaling in both the partners. Among plant–microbe interactions, symbiotic associations of arbuscular mycorrhizal fungi (AMF) and arbuscular mycorrhizal-like fungus especially Piriformospora indica with plants are well known to improve plant growth by alleviating the stress-impacts and consequently enhance the plant fitness. AMF and P. indica colonization mainly enhances ROS-metabolism, maintains ROS-homeostasis, and thereby averts higher ROS-level accrued inhibition in plant cellular processes and plant growth and survival under stressful environments. This article summarizes the major outcomes of the recent reports on the ROS-generation and scavenging and signaling in biotic-abiotic stressed plants with AMF and P. indica colonization. Overall, a detailed exploration of ROS-signature kinetics during plant-AMF/P. indica interaction can help in designing innovative strategies for improving plant health and productivity under stress conditions.